2004
DOI: 10.1002/art.20103
|View full text |Cite
|
Sign up to set email alerts
|

Is α‐actinin a target for pathogenic anti‐DNA antibodies in lupus nephritis?

Abstract: Objective. Following recent reports that pathogenic murine anti-DNA antibodies bind to ␣-actinin, it was obviously of interest to assess the ability of human pathogenic anti-double-stranded DNA (anti-dsDNA) antibodies to bind this antigen. Both human monoclonal anti-DNA antibodies and antibodies affinity purified from the sera of patients with systemic lupus erythematosus (SLE) were investigated.Methods. An enzyme-linked immunosorbent assay was established to measure immunoglobulin binding to ␣-actinin. Antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
71
1
3

Year Published

2005
2005
2007
2007

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 13 publications
5
71
1
3
Order By: Relevance
“…This finding is in contrast with a recent report of the weak expression of anti-␣-actinin antibodies in kidney eluates from (NZB ϫ NZW)F 1 mice (11). Thus, our data confirm the presence of serum antibodies to ␣-actinin in SLE (19,20) but not their nephritogenic potential. In contrast, the present IEM analyses revealed antibodies deposited in electrondense structures associated with the GBM in both the early stages of nephritis (Kalaaji M, et al: unpublished observations) and the advanced stages of nephritis.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This finding is in contrast with a recent report of the weak expression of anti-␣-actinin antibodies in kidney eluates from (NZB ϫ NZW)F 1 mice (11). Thus, our data confirm the presence of serum antibodies to ␣-actinin in SLE (19,20) but not their nephritogenic potential. In contrast, the present IEM analyses revealed antibodies deposited in electrondense structures associated with the GBM in both the early stages of nephritis (Kalaaji M, et al: unpublished observations) and the advanced stages of nephritis.…”
Section: Discussionsupporting
confidence: 62%
“…Recently, antibodies to ␣-actinin, a major structural component of glomerular podocytes and mesangial cells (17,18), have attracted particular attention, because ␣-actinin may represent a target molecule for nephritogenic anti-dsDNA antibodies (10,11,19,20).…”
mentioning
confidence: 99%
“…Two groups have shown that binding to ␣-actinin is an important factor in the pathogenicity of anti-dsDNA antibodies in mouse models (9,10,35). These results were supported in a clinical study (32). No group has previously published an analysis of effects of somatic mutations in human anti-dsDNA antibodies on ability to bind ␣-actinin.…”
Section: Lambrianides Et Almentioning
confidence: 94%
“…The direct ELISAs used to detect binding of IgG molecules to ␣-actinin, cardiolipin, and ␤ 2 GPI have been described previously (25,32). The assay for IgG binding to cardiolipin was performed using fetal calf serum (FCS) containing ␤ 2 GPI.…”
Section: Lambrianides Et Almentioning
confidence: 99%
“…Purified anti-dsDNA antibodies from patients with SLE showed cross-reactivity with α-actinin and this was most commonly observed in patients with lupus nephritis (285). This argument was strengthened by demonstrating an association between antibody affinity for α-actinin and binding to glomeruli in vitro (286) .…”
Section: Discussionmentioning
confidence: 98%